Long-term Management of Homozygous Protein C Deficiency: Replacement Therapy with Subcutaneous Purified Protein C Concentrate - Sanz-Rodriguez, C.; Gil-Fernández, J. J.; Zapater, P.; Pinilla, I.; Granados, E.; de Soria, V. Gómez-G.; Cano, J.; Sala, N.; Fernández-Rañada, J. M.; Gómez Gómez, N. (Thrombosis and Haemostasis, 1999)
We present the case of a full-term newborn in whom purpura fulminans developed shortly after birth. A diagnosis of homozygous protein C deficiency was established based upon undetectable plasma protein C activity and antigenemia in the newborn infant, and was later confirmed by protein C gene analysis. Specific replacement therapy with intravenous protein C concentrate was started 9 days after birth. This rapidly led to the complete regression of cutaneous lesions and consumption coagulopathy. After stabilization, oral anticoagulation was initiated in association with prophylactic treatment with intravenous protein C concentrate. However, oral anticoagulation was finally abandoned as the patient presented several thrombotic and hemorrhagic episodes clearly related to difficulties with anticoagulation. Due to the hazards related to prolonged venous access, we are currently using subcutaneous infusion of protein C concentrate for the longterm management of this condition, with satisfactory results.